Free-Movement Rights of Third Country Nationals in the EU Internal Market - Bazylińska-Nagler, Justyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Integration of third-country nationals who may be: long-term residents, EU citizens’ family members, students, researchers, highly qualified employees, or even seasonal workers in member states, is crucial for the EU economic and social cohesion. In order to constitute a genuine instrument for the TCNs integration into the society where they live, they should enjoy equality of treatment with EU citizens in a variety of economic and social matters. Through this work I would like to share some doubts and questions over crucial points of the architecture of the EU system of protection of fundamental rights applied to TCNs, which is uniquely complex.
Keywords: prawo do swobodnego przemieszczania się; obywatele państw trzecich; rezydenci długoterminowi; studenci; naukowcy; wysoko wykwalifikowani pracownicy; członkowie rodziny